Förändringar och nya riktningar inom human service - Berg, Elisabeth (Luleå tekniska universitet, Arbetsvetenskap, 2010)
Validerad; 2011; Bibliografisk uppgift: Artiklar från Dilemmas for Human Services 2010 Changes and new directions in Human Services 14th International Research Conference To be hosted by Luleå University of Technology 10 - 11 September 2010; 20110329 (elbe)